Clinical complications in envenoming by Apis honeybee stings: insights into mechanisms, diagnosis, and pharmacological interventions - Cavalcante, Joeliton S.; Riciopo, Pedro Marques; Pereira, Ana Flávia Marques; Jeronimo, Bruna Cristina; Angstmam, Davi Gomes; Pôssas, Felipe Carvalhaes; Andrade Filho, Adebal de; Cerni, Felipe A.; Pucca, Manuela B.; Ferreira Junior, Rui Seabra (Frontiers in Immunology, 2024)
Envenoming resulting from Apis honeybee stings pose a neglected public health concern, with clinical complications ranging from mild local reactions to severe systemic manifestations. This review explores the mechanisms underlying envenoming by honeybee sting, discusses diagnostic approaches, and reviews current pharmacological interventions. This section explores the diverse clinical presentations of honeybee envenoming, including allergic and non-allergic reactions, emphasizing the need for accurate diagnosis to guide appropriate medical management. Mechanistic insights into the honeybee venom's impact on physiological systems, including the immune and cardiovascular systems, are provided to enhance understanding of the complexities of honeybee sting envenoming. Additionally, the article evaluates emerging diagnostic technologies and therapeutic strategies, providing a critical analysis of their potential contributions to improved patient outcomes. This article aims to provide current knowledge for healthcare professionals to effectively manage honeybee sting envenoming, thereby improving patient care and treatment outcomes.